2000
DOI: 10.1152/ajpgi.2000.279.4.g740
|View full text |Cite
|
Sign up to set email alerts
|

Nitrergic and purinergic regulation of the rat pylorus

Abstract: The role of nitric oxide (NO) and ATP in the regulation of nonadrenergic, noncholinergic (NANC) inhibitory transmission in the pylorus remains unclear. In the presence of atropine and guanethidine, electric field stimulation induced NANC relaxations in a frequency-dependent manner (1-20 Hz) in the rat pylorus. NANC relaxations were significantly inhibited by N(G)-nitro-L-arginine methyl ester (L-NAME; 10(-4) M). P(2X) purinoceptor antagonist pyridoxal phosphate-6-azophenyl-2',4'-disulfonic acid (PPADS; 3 x 10(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 42 publications
(62 reference statements)
3
25
0
Order By: Relevance
“…We found that the apamin-sensitive component of EFS relaxation is strongly inhibited by MRS 2179, showing that a purine mediates this component by acting on P2Y 1 receptors; it is slightly but consistently inhibited by NF 279, also suggesting the involvement of P2X 1,2,3 receptors; and it is slightly inhibited by the peptidase chymotrypsin, suggesting that PACAP (an apamin-sensitive peptidergic neurotransmitters) also has a minor role in EFS-induced relaxation. Similar results on the involvement of P2Y1 and also P2X 1,2,3 receptors on inhibitory neurotransmission were found in the mouse jejunum (De Man et al, 2003), and ATP-induced relaxation of rat pylorus has been attributed to muscular P2X purinoceptors (Ishiguchi et al, 2000). Heme oxygenase inhibitors did not modify Fig.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…We found that the apamin-sensitive component of EFS relaxation is strongly inhibited by MRS 2179, showing that a purine mediates this component by acting on P2Y 1 receptors; it is slightly but consistently inhibited by NF 279, also suggesting the involvement of P2X 1,2,3 receptors; and it is slightly inhibited by the peptidase chymotrypsin, suggesting that PACAP (an apamin-sensitive peptidergic neurotransmitters) also has a minor role in EFS-induced relaxation. Similar results on the involvement of P2Y1 and also P2X 1,2,3 receptors on inhibitory neurotransmission were found in the mouse jejunum (De Man et al, 2003), and ATP-induced relaxation of rat pylorus has been attributed to muscular P2X purinoceptors (Ishiguchi et al, 2000). Heme oxygenase inhibitors did not modify Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Smooth muscle cells along the gastrointestinal tract can simultaneously express G-protein-coupled P2Y receptors mediating the relaxatory effects of purines and ion-gated P2X receptors mediating either contractions (Giaroni et al, 2002) or relaxations (Storr et al, 2000). Activation of P2X receptors could initially induce an increase in intracellular Ca 2ϩ leading a contraction and a relaxation as a result of secondary activation of apamin-sensitive Ca 2ϩ -dependent K ϩ -channels (Ishiguchi et al, 2000). MRS 2179 is a specific antagonist for P2Y 1 purinoreceptor subtype (De Man et al, 2003) that in our study strongly antagonized the ATP relaxation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent study showed that NANC relaxations were significantly inhibited by L-NAME, suggesting the mediation by neuronal release of NO (Ishiguchi et al 2000b). …”
Section: In Vitro Recording Of Pyloric Relaxationmentioning
confidence: 97%
“…Soediono and Burnstock (1994) have concluded that ATP seems to act through P 2Y -purinoceptors in the rat pyloric sphincter. Studies on the rat pylorus by Ishiguchi et al (2000) have also shown that NO and ATP act in concert to mediate NANC relaxation. However, these authors suggested that P 2X purinoceptors are involved in the ATP-induced relaxation.…”
Section: Cotransmitters Responsible For Nonadrenergic Noncholinergmentioning
confidence: 99%